Pengaruh citra merk dan celebrity endorsment terhadap keputusan pembelian produk skincare wardah pada generasi z (studi kasus di kota denpasar) - Ni Made Enayanti; Ni Ketut Sukanti (STIMI Handayani Denpasar, 2023)
This study aims to determine the effect of brand image and celebrity endorser on purchasing decisions for Wardah skincare products in Denpasar City. This study uses a quantitative approach. The data used are skincare review viewer data and local brand sales data in e-commerce in 2021, the sample testing technique is carried out through a sampling method that uses classical assumption testing, determination analysis, linear multiple analysis, partial (t-test) and simultaneous testing. (f-test). The results of this study prove that brand image has a positive and significant effect on purchasing decisions, celebrity endorsers have a positive and significant effect on purchasing decisions. Simultaneously brand image and celebrity endorser have a significant effect on purchasing decisions.